Adolescent volunteerism and its contribution to social and moral development as perceived by the UPLB Ugnayan ng Pahinungod student volunteers - Lalap, B. A.; Saguiguit, S. L. C.; Dizon, J. T. (2003)
This study was conducted to determine the relationship between the adolescents' demographic and personal attributes with their motivations for volunteerism, especially: self- esteem, social motivations for volunteerism, especially: self-esteem, social relationship, reciprocity, recognition, and career development. The respondents' perceived contributions of volunteering to their social and moral developmental domains were also determined. Fifty UPLB Ugnayan Pahinguhod student volunteers aged 16 to 21 years old were asked to accomplish self-administered questionnaires. Age, student classification, religious involvement, birth order, and empathy were found to have weak correlations with self-esteem and social relationships. Personal distress was established to have significant relationships with career development. Both sexes were motivated to volunteer by self-esteem, recognition, reciprocity, and career development. According to the responsibilities, volunteering enhanced their social skills, sense of responsibility, open mindedness, and compassion.
Keywords: Volunteerism; Social development; Moral development; Student volunteers in social service; University of the Philippines (Los Baños). Ugnayan ng Pahinungod